Psychometric properties, validity and insights of the School Bullying Questionnaire (CIE-A) in secondary schools of the Valencian Community (Spain). - Sergio A Useche (Public Library of Science (PLoS), 2021)
Besides its several threats to health, welfare, social and academic development and performance of kids and teenagers, school bullying remains highlighted as one of the most relevant related challenges for educational, behavioral and legal sciences worldwide. Moreover, the lack of research on the field and the crucial but unattended need to count on psychometrically suitable and valid tools to detect school bullying make difficult understanding its contexts, dynamics and possible solutions. Objective The aim of this study was to thoroughly present in detail the psychometric properties and validity issues of the School Bullying Questionnaire (CIE-A) among secondary students. Methods A regionwide sample of 810 (47.2% girls) secondary students attending to 21 schools across the Valencian Community (Spain), aged M = 14.40 (SD = 1.61) years, responded to a paper-based questionnaire containing the 36-item version of the CIE-A and various scales related to psychosocial health and wellbeing, used as criterion variables. Results The outcomes of this study suggest that the CIE-A has a clear factor structure, an optimal set of item loadings and goodness-of-fit indexes. Further, that CIE-A has shown good internal consistency and reliability indexes, coherent associations with other mental health and academic performance variables, and the possibility to assess gender differences on bullying-related factors among secondary students. Conclusion The CIE-A may represent a suitable tool for assessing bullying in a three-factorial approach (i.e., victimization, symptomatology, and intimidation), offering optimal psychometric properties, validity and reliability insights, and the potentiality of being applied in the school environment. Actions aimed at improving the school coexistence and the well-being of secondary students, targeting potential bullied/bully profiles or seeking to assess demographic and psychosocial correlates of bullying among teenagers, might get benefited from this questionnaire.